THE INFLUENCE OF CYCLE LEARNING MODEL INTEGRATED BY THINK PAIR SHARE AND STUDENT TEAM ACHIEVEMENT DIVISSION ON QUALITY OF PROCESSES AND COGNITIVE LEARNING OUTCOMES - Sholikah, Amar Atus; Zubaidi, Nanang (Universitas Negeri Surabaya, 2020)
Hydrocarbons are one of the materials from Chemistry that studies abstract concepts and procedural knowledge such as alkanes, alkenes and alkyas. To study hydrocarbon material, students must master well the concepts related to previous concepts such as the concept of covalent bonding and equalizing reactions. If students do not understand the concepts related to hydrocarbon material, it will be difficult to master the concepts in hydrocarbon material. The learning process at school at this time sometimes also still does not increase student creativity and activity. The application of the Learning Cycle 5E learning model combined with cooperative type TPS (Think Pair Share) and cooperative type STAD can be used as an alternative to developing a more meaningful learning atmosphere in understanding concepts and giving students the opportunity to work together to solve problems. The purpose of this study was to determine: the quality of the learning process using the LC 5E - TPS and LC 5E - STAD models on the topic of hydrocarbons, as well as differences in the cognitive learning outcomes of hydrocarbon students who were taught with these two learning models. This study uses a quasi-experimental design with